Implementasi Gerakan Literasi Al-Qur’an di Madrasah Ibtidaiyah Negeri 6 Brebes - Adella Syaharani; Dedi Romli Triputra; Laelia Nurpratiwiningsih (Peneliti.net, 2022)
Al-Qur'an literacy is the skill of mastering reading the Qur'an, but not only reading, but also writing and understanding the meaning contained in the Qur'an. To build a sense of love for the Qur'an from an early age, a Qur'an literacy movement program was held at Madrasah Ibtidaiyah Negeri 6 Brebes. The purpose of this study is to describe the implementation of the Al-Qur'an literacy movement at MIN 6 Brebes, and describe the obstacles that occur in the Implementation of the Al-Qur'an Literacy Movement at MIN 6 Brebes. This study uses qualitative research. Data collection techniques from this study are in the form of observation, interviews, and documentation. The validity of the data is done by using triangulation, namely source triangulation and technical triangulation. The implementation of the Al-Qur'an literacy movement in grade 2 MIN 6 Brebes is still at an early stage, which is still in the process of learning Iqra, volumes 3 to 4. The obstacles in implementing the Al-Qur'an literacy movement are more focused on obstacles when online, by Therefore, it is hoped that there will be attention from parents to cooperate with class teachers so that grade 2 students are able to read, write, and memorize the Qur'an well.